THE ROLE OF PHYSICAL AND SPECIAL TRAINING IN WRESTLERS (World Bulletin of Physical Education and Sports Science, 2026)
This article provides a brief overview of the role of physical and special training in wrestlers.
Keywords: Wrestling, training, sport, form, skill, technique, tactics, result.